Validation of a food waste behaviour questionniare among households: a Malaysian context / Sarah Ainina Mohd Nazi, Zuraini Mat Issa @ Zakaria and Saidatul Afzan Abdul Aziz - Mohd Nazi, Sarah Ainina; Mat Issa @ Zakaria, Zuraini; Abdul Aziz, Saidatul Afzan (2022)
Food waste affects the food security status especially among the low-income groups. In addition, food wastage influences the financial development of the country where the economic cost of the industries will be at loss, equivalent to the waste of food that occurs during food production. In Malaysia, households have been identified as the main contributor to this food wastage amounting to approximately 16,650 tons of food is wasted daily. Hence, this preliminary study will validate the instrument used in examining factors influencing the household's food waste that contribute to the food waste behaviour. In addition, this study also will evaluate the reliability of the instrument used. A purposive sampling was applied to collect data via online survey among 50 households in Selangor. The data were subjected to SPSS version 26 for reliability analyses. The results showed that all dimensions are between the values of 0.6 to 0.9. According to the Alpha Coefficient Range, these values can be considered moderate, good and very good. Therefore, the instrument developed is valid and reliable and can be used for actual data collection involving households in Kuala Lumpur. The study will be extended to other parts of the country. The findings of this study can be used by the local authorities in providing new guidelines, and in educating and providing suitable intervention among Malaysian citizens related to food waste management. Besides, the outcomes of the study will help the researchers and relevant bodies to understand how people manage food to avoid wastage and ensure food security among family members.